Pengembangan Desa Wisata Cikolelet dari Perspektif Community Service Perguruan Tinggi - Rahmawati Rahmawati; Muhamad Kurniawan; Ayuning Budiati (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
Higher education institutions play a key strategic role in developing tourism villages by fulfilling the Tri Dharma mandate, which includes education, research, and community service activities conducted by lecturers and students. The Cikolelet tourism village, the first in Serang Regency, has emerged as a model for such engagement, particularly for community service and research initiatives. This study analyzes how universities in the Banten area have contributed community service activities to the development of Cikolelet tourist village. Using a descriptive qualitative method and purposive sampling of informants actively involved in Cikolelet’s development, the research highlights that universities specializing in tourism have pioneered its transformation, guiding Cikolelet from its planning stage as a tourism village to its current status as a pilot and fostered village. While other universities have engaged Cikolelet as a site for research and community service, challenges remain: university programs often prioritize their own agendas over the specific development needs of Cikolelet village. This misalignment limits the impact and sustainability of interventions. For more successful development, research and community service should be tailored to Cikolelet’s priority needs, ensuring long-term benefits to the village and its community.